Monte-Carlo simulation of random hyperbranched polymers with flexible branches - Ratner, M. (Functional Materials, 2009)
Monte-Carlo simulation of random hyperbranched polymers with flexible branches was conducted. It was shown that such polymers demonstrate universal conformational properties. In particular, there exist a critical hyperbranched polymer generation number Gcr ≈ 6 at which the transfer occurs from coil-type structure with scaling properties similar to those of linear polymer coil to fractal structure. The fractal dimension dfr ≈ 3 is universal independently on details of random hyperbranched polymer internal building. It is shown that system entropy is of Tsallis type.